2012
DOI: 10.1002/fuce.201100184
|View full text |Cite
|
Sign up to set email alerts
|

Operating Temperature Dependency on Performance Degradation of Direct Methanol Fuel Cells

Abstract: The effect of operating temperature on performance degradation of direct methanol fuel cell (DMFCs) is examined to disclose the main parameter of the degradation mechanism and the degradation pattern in the membrane electrode assemblies (MEAs). The DMFC MEA degradation phenomenon is explained through the use of various electrochemical/physicochemical tools, such as electrochemical impedance spectroscopy, electrode polarization, methanol stripping voltametry, field emission‐scanning electron microscopy, X‐ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Bae et al [178] investigated the long-term durability of DMFC at three different working temperatures 60, 70 and 80 C for 200e300 h. There were larger irrecoverable performance losses observed at the higher working temperatures which expedited the MEA failures as estimated using a biexponential model. As already mentioned in a previous section, Park et al [61] observed a pinhole formation in Nafion ® 115 membrane during a long-term test of DMFC operating at 80 C that caused a quick voltage decline, while no such issue was encountered for the operational temperature of 60 C. The choice of high working temperatures for DMFC, on one side, is useful to tackle mass-transport related issues such as cathode flooding that causes a temporary performance decay, but on the other side, it brings about adverse consequences as far as stability of component materials is concerned. This not only gives rise to a permanent performance loss but also shortens the MEA lifetime.…”
Section: Operating Conditionsmentioning
confidence: 70%
See 1 more Smart Citation
“…Bae et al [178] investigated the long-term durability of DMFC at three different working temperatures 60, 70 and 80 C for 200e300 h. There were larger irrecoverable performance losses observed at the higher working temperatures which expedited the MEA failures as estimated using a biexponential model. As already mentioned in a previous section, Park et al [61] observed a pinhole formation in Nafion ® 115 membrane during a long-term test of DMFC operating at 80 C that caused a quick voltage decline, while no such issue was encountered for the operational temperature of 60 C. The choice of high working temperatures for DMFC, on one side, is useful to tackle mass-transport related issues such as cathode flooding that causes a temporary performance decay, but on the other side, it brings about adverse consequences as far as stability of component materials is concerned. This not only gives rise to a permanent performance loss but also shortens the MEA lifetime.…”
Section: Operating Conditionsmentioning
confidence: 70%
“…The presumable reasons for the detachment of electrodes from the membrane include increased mechanical stress at the interface due to swelling and contraction of the membrane [9,61], generation of CO 2 gas at the anode [58], heat generation at the cathode [61], use of concentrated methanol feed [81], and dissolution of Nafion ® ionomer present at the interface [54].…”
Section: Degradation Of Mea Structure and Morphologymentioning
confidence: 99%
“…It can be seen that the morphology of CCM sample changes obviously after long‐term test. Noticeably, the as‐prepared MEA shows a much more compact and continuous contract between membrane and catalyst layers than that of MEA after testing for 3,000 h. After 3,000 h, a clear boundary and many obvious cracks appeared between the interface of cathode layer and membrane, and the morphological change in the anode side is more serious than that of cathode side, which may be explained for the solubility of Nafion ® membrane and Nafion ® ionmer in the catalyst layer , . The clear boundary between membrane and catalyst layers would lead to an increased contact resistance between the membrane and the catalyst layers or between the catalyst layers and the diffusion layers, resulting in an resistance increase in the stability test.…”
Section: Resultsmentioning
confidence: 99%
“…123 At higher temperatures, the rate of degradation is higher due to the formation of pinholes in the membrane in concert with delamination and degradation of cathode. 124 Also, at higher temperatures, ruthenium dissolution/ leaching from PtRu/C is accelerated when the anode experiences potential greater than 0.363 V versus DHE. 120 The DMFC performance and durability data are summarized in Table 4 .…”
Section: Mea Fabricationmentioning
confidence: 99%